1996
DOI: 10.1002/stem.140558
|View full text |Cite
|
Sign up to set email alerts
|

Serum Thrombopoietin Level in Various Hematological Diseases

Abstract: Abstract. To investigate the pathophysiological role of thrombopoietin (TPO) in thrombopoiesis, we measured its serum levels in 15 healthy individuals, 84 patients with various hematological diseases and 2 patients with liver cirrhosis using an enzyme immunoassay procedure. The TPO level was 0.84 ± 0.40 f mol/ml in normal individuals. TPO levels were considerably elevated in patients with myelosuppression after intensification chemotherapy of acute leukemia in complete remission (postchemotherapy group; n = 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
28
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 41 publications
6
28
0
Order By: Relevance
“…It has been proposed, based on TPO levels in patients with aplastic anemia and idiopathic thrombocytopenic purpura, that the serum TPO levels were inversely correlated with total platelet mass. 6 This case illustrates a dysregulation in the relationship between platelet mass and serum TPO levels, and is consistent with observations reported in patients with essential thrombocytopenia, 7,8 suggesting a neoplastic disorder driven by dysregulated TPO production. No relationship between TPO levels and the platelet count was observed in patients with other myeloproliferative disorders.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…It has been proposed, based on TPO levels in patients with aplastic anemia and idiopathic thrombocytopenic purpura, that the serum TPO levels were inversely correlated with total platelet mass. 6 This case illustrates a dysregulation in the relationship between platelet mass and serum TPO levels, and is consistent with observations reported in patients with essential thrombocytopenia, 7,8 suggesting a neoplastic disorder driven by dysregulated TPO production. No relationship between TPO levels and the platelet count was observed in patients with other myeloproliferative disorders.…”
Section: Discussionsupporting
confidence: 85%
“…No relationship between TPO levels and the platelet count was observed in patients with other myeloproliferative disorders. 8 The origin of the neoplastic clone in post-transplant malignancies has been determined by different methods, including white blood cell isoenzyme polymorphisms, routine and multi-parameter fluorescence in situ hybridization (FISH) karyotypic analyses, 9 and DNA polymorphisms recognized by restriction endonuclease digestion and Southern blot hybridization or polymerase chain reaction analyses. 10 The identification of a highly polymorphic genetic locus in the human genome makes it possible to distinguish individual genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Serum concentrations of endogenous TPO (eTPO) reflect its constitutive production by the liver and its clearance through binding and internalization by Mpl, the TPO receptor found on the surfaces of platelets and megakaryocytes [10,11]. Several studies have reported increased amounts of eTPO in patients with thrombocytopenia secondary to aplastic anemia, amegakaryocytic thrombocytopenia, and myeloablative chemotherapy [12][13][14][15][16][17][18][19]. In contrast, eTPO levels are not increased in patients with ITP, despite the markedly reduced number of circulating platelets [14][15][16]20].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, anagrelide was effective, even though we detected a thrombopoietin serum concentration only marginally above normal. 6 Allogenic hematopoietic stem cell transplantation from his HLA-identical brother (10/10-Ag) was performed 60 days after diagnosis using FLAMI/RIC conditioning (fludarabine 30 mg/m 2 , days 1-4, cytarabine 2,000 mg/m 2 , days 1-4, mitoxantrone 10 mg/m 2 , days 1-4, total body irradiation 4 Gy, day 8, cyclophosphamide 60 mg/m 2 , days 9-10). Therapy associated complications included neutropenic fever, BK-virus associated cystitis and a severe mucositis (common toxicity criteria [CTC] grade III/IV).…”
Section: Case Reportmentioning
confidence: 99%